Urgensi Pendekatan Personal Dalam Meningkatkan Hasil Belajar Aqidah Akhlak Pada Peserta Didik Di Kelas IV MI Datuk Sulaiman Putra Palopo - Nur Ainun; Hasriadi Hasriadi; Subhan Subhan (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Urgency of a Personal Approach in Improving the Learning Outcomes of Aqidah Akhlak in Students in Class IV Mi Datuk Sulaiman Putra Palopo This research is motivated by the finding that fourth-grade students at MI Datuk Sulaiman Putra Palopo have not yet achieved mastery of Akidah Akhlak learning due to minimal attention to individual differences. This study aims to describe the implementation of a personal approach, identify the factors that influence it, and characterize students through this approach. The method used is qualitative research with a phenomenological approach through observation, interviews, and documentation. The results of the study indicate that the implementation of a personal approach is carried out in three stages: planning, implementation, evaluation and follow-up. Factors that influence its implementation consist of internal and external factors. The implementation of a personal approach has a positive impact on learning outcomes, as indicated by an increase in the average score to 85.5, 100% mastery, and positive behavioral changes among students. The interpretation of the results confirms that an effective personal approach improves holistic learning outcomes and helps teachers recognize students' individual characteristics.